การมีส่วนร่วมของชุมชน ในการพัฒนาตำบลต้นแบบด้านการดูแลสุขภาพผู้สูงอายุระยะยาว ตำบลธาตุ อำเภอวารินชำราบ จังหวัดอุบลราชธานี - Sriproma, Satawat; Promsattayapoj, Worapoj; Teewanda, Danai (Academic Journal of Thailand National Sports University, 2022)
Development of the model sub-district according to a standard of the elderly care is the highest goal of a long term health care system involving a participation from a community network. The present research aimed to study a community participation in developing a model of the long run health care system for the elderly in Tambon Tat in Warinchamrap district of Ubon Ratchathani province. A total of 54 research participants comprised Tambon administrative organization mayors, members of Tambon administrative organizations, community leaders, a Tambon chief, village chiefs, committees of the public health volunteer club and volunteers for the elderly care. The samples were specifically selected. A total of 110 elderly were recipients of the benefits. Data were collected by the interviews and the focus group form. Data were analyzed by percentage, mean, standard deviation and content analysis. The findings revealed that there were 6 stages of the developmental process: 1) appointing a research team; 2) exploring the basic data; 3) having meeting for workshop planning; 4) acting through the operational plan; 5) supervising, following up, and evaluating the outcomes; and 6) summarizing the findings as Double - CAMP. Committee, Communication, Administrator, Ability, Money, Motivation, Planning, Participation, The findings showed overall the high coordination among the participants for the development. The elderly were satisfied in the development of the elderly care at the service center and at home. It also revealed the high degree of quality in public health staff. Subsequently, this operational plan obtained the standard of the development as the sub-district model in a long term health care for the elderly in accordance with the Public Health Department as the excellent degree. In summary, the achieving factors of this study can be identified by the development of working motivation, development of potential working team, and the committee.